(untitled) (Journal of the College of Basic Education, 2023)
Perhaps we do not ignore the truth if we say that a person’s interest in art is no less important than his interest in science, because science and art are two products that represent the axes of his life that cannot be dispensed with either of them. And if we set aside the discussion of science and limit it to art, we say that the fine arts were and still are tools for expressing man’s emotions towards existence, and he tries through them to find a balance for his different feelings. To the ideal image that nature should have, because art is "a process of creation and innovation under a law and system of formal relationships that deal with human conscience, and the artist does not accomplish his artistic work except through conflict, opposition, and intense interaction."The fine arts, whatever their sources in the field of human struggle, become through talent and presentation technique a different fieldPerhaps it is useful in this research to leave the discussion of fine arts in general and to single out poetry and painting - and it seems that the relationship between them is an ancient matter in human thought. Like the painters, "it is the oldest reference to this relationship. In talking about this relationship, Demizat and Brooks say that there is an emphasis on the integration between poetry and painting, and a literary influence in drawing on the one hand, and control of drawing in minimal expression on the one hand. In other words, the confirmation of the pictorial influence in literature and aesthetic congruence Between poetry and painting, as is the case with the French artist Charles Alphonse Eddie in the classical era, in a treatise entitled “The Art of Painting” that parallels Horace’s “The Art of Poetry” and “The Art of Poetry.”